2011
DOI: 10.1007/s00595-011-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Digital evaluation of the muscle functions of the lower extremities among inguinal hernia patients treated using three different surgical techniques: a prospective randomized study

Abstract: Use of a digital environment with numerical parameters and measurements recorded using a dynamometer demonstrated that in the early postoperative period and on the third postoperative day, open surgery causes more functional loss in the lower extremities than laparoscopic methods. Therefore, surgeons should use laparoscopic methods whenever possible to reduce both pain and loss of muscle function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The most recent meta-analysis for comparison of TEP with TAPP by Chen [49] with 1519 randomized patients included six further RCTs by Ciftci [57], Mesci [58], Sharma [59], Günal [60], Bansal [61] and Jeelani [62]. But five of these six additional RCTs included women, recurrences or bilateral inguinal hernias [57-59, 61, 62] and therefore had to be excluded from the present analysis.…”
Section: Comparison Of Tep Vs Tapp In Meta-analyses and Rctsmentioning
confidence: 99%
“…The most recent meta-analysis for comparison of TEP with TAPP by Chen [49] with 1519 randomized patients included six further RCTs by Ciftci [57], Mesci [58], Sharma [59], Günal [60], Bansal [61] and Jeelani [62]. But five of these six additional RCTs included women, recurrences or bilateral inguinal hernias [57-59, 61, 62] and therefore had to be excluded from the present analysis.…”
Section: Comparison Of Tep Vs Tapp In Meta-analyses and Rctsmentioning
confidence: 99%
“…These trials usually covered both direct and indirect hernia, and there was only one trial targeted only direct hernia (8). Most trials included unilateral hernia and bilateral hernia (5,6,(10)(11)(12)14,20,23), and five of the included trials purely investigated unilateral hernia (7,9,21,22,24). Table 1 showed relevant information of these trials, and quality of these trials was performed in concerned due to insufficient information in randomization sequence and concealment, no blinding to health providers, and about 15% lost follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…A t o t a l o f s e v e n t r i a l s ( n = 8 8 2 ) r e p o r t e d s e r o m a (5,9,10,12,14,20,23), and four of the seven trials mainly focused on primary hernia repairment (n=603) (9,12,14,20). Overall pooled results showed that TEP led to higher seroma rate than TAPP (POR=2.01; 95% CI, 1.39 to 2.91; I-square =9%; Figure 2).…”
Section: Seromamentioning
confidence: 99%
See 2 more Smart Citations